Effect of sodium hydroxide concentration on properties of carboxymethyl rice starch - Rachtanapun P. (2014)
Effect of sodium hydroxide (NaOH) concentrations on properties of carboxymethyl rice starch (CMS r) was investigated. Fourier transform-infrared (FTIR) spectrum confirmed that carboxymethylation took place on the starch molecules. The DS value of CMS r increased with increasing NaOH concentrations (10-40% w/v). However, when the level of NaOH concentration reached 50%, the DS of the CMS decreased. The viscosity of CMS r decreased with increasing NaOH concentrations. The morphology of native rice starch and CMS r was further investigated through scanning electron microscope (SEM). The mirco-structure revealed that the morphology of CMS r granules were more damage with increasing NaOH concentration which related with DS.